Carbonaceous materials are not suitable catalysts for direct NO decomposition in exhaust aftertreatment. Issue 6 (25th February 2022) - Vennewald, Maurice; Iemhoff, Andree; Ditz, Daniel; Palkovits, Regina
Abstract : New approaches for direct NO decomposition catalysis are urgently needed, but using carbonaceous supports appears not to be the way to go. Abstract : Carbonaceous materials have been suggested as catalysts for direct NO decomposition. In contrast to previous reports, it is demonstrated herein that even graphitic carbon nitride (g-CN) (stable in air up to 600 °C; valence band potential of 1.9 V) is not a catalyst but instead reacts stoichiometrically with NO to form isocyanic acid at temperatures higher than 450 °C.